Sovereign choices and sovereign constraints : judicial restraint in investment treaty arbitration - Van Harten, Gus (Oxford : Oxford University Press, 2014)
The role of investment arbitration is a controversial issue, as it is increasingly seen as a system in which private arbitrators adjudicate on the public law decisions of states. This book provides an empirical study of the function of investment arbitration, how it is impacting on international law, and the ways in which it is in need of reform.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 13, 2013).
Keywords: Investments, Foreign -- Law and legislation; Arbitration and award, International; Commercial treaties